KEDUDUKAN ANAK KANDUNG SEBAGAI AHLI WARIS PADA SISTEM PEWARISAN DALAM PERKAWINAN PADA GELAHANG DI DESA ADAT BATUAN GIANYAR (DALAM PERSPEKTIF HUKUM ADAT BALI) - Desak Made Dwipayani; Dewa Bagus Sanjaya; Ni Ketut Sari Adnyani (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
This study aims to determine (1) The process of implementing marriage in gelahang in Batuan Traditional Village, Sukawati District, Gianyar Regency, (2) The position of biological children as heirs in the inheritance system in marriage in gelahang in Batuan Traditional Village, Sukawati District, Gianyar Regency. This type of research uses empirical juridical methods. The sample collection technique uses Purposive sampling. The subject of the study was a community in Batuan Traditional Village, Sukawati District, Gianyar Regency. The object of the study is the customary rules regarding marriage in gelahang, it must be emphasized to provide legal certainty to the status of those who perform marriages on gelahang and the position of children born from such marriages. The data collection techniques used in the research are document study techniques, interview techniques and observation techniques. The collected data are analyzed descriptively qualitatively. The results of this study show that (1) The marriage process in gelahang is the same as ordinary marriage, the only difference is in the marriage in gelahang before marriage, an agreement is made where the agreement is made by the families of both parties of the bride and groom, (2) The position of biological children as heirs in the inheritance system in marriage in gelahang in Batuan Traditional Village that is, based on the agreement that has been made by the families of both parties of the bride and groom.